Optimisation of pH and Dosage of Banana Peel Activated Carbon in Removing Colour From Textile Wastewater - Abu Bakar, Norshila; Othman, Norzila; Wanja, Nur Atikah Erna (Recent Trends in Civil Engineering and Built Environment, 2020)
Textile wastewater is one of contributors to water pollution. Many stages have been involved in the processing of textiles, and most of the process generated wastewater. The wastewater contains chemical substances and colouring agents that may affect to water pollution. However, problem-related to textile wastewater is the high concentration of colour from dyes stuff, i.e., harmful to surrounding, especially human and environment. Improper treatment of the textile wastewater happened when the wastewater discharges to the receiving environment. This study was conducted to optimise pH and dosage in removing colour from the textile wastewater. Adsorption method was applied to reduce the concentration of colour in effluents. Activated carbon from banana peel was used to get the optimum value of pH and dosage by using batch study experiment. The result of removal colour by using DR6000 Spectrophotometer was used to analysis colour obtained, the optimum value of pH and dosage for removal of colour from the textile sample are found to be at pH 8, and the amount of dosage is 4g. It shows that by using banana peel activated carbon it can improve the textile wastewater treatment for colour removal.